Thermal sensors based on delafossite film/p-silicon diode for low-temperature measurements - Elgazzar, Elsayed; Tataroglu, A.; Al-Ghamdi, Ahmed A.; Al-Turki, Yusuf; Farooq, W. A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2016)
A CuFeO2 film was prepared on p-type silicon wafer to fabricate an Al/CuFeO2/p-Si/Al diode by the sol-gel method. The temperature and frequency dependence of electrical characteristics of Al/CuFeO2/p-Si/Al diode were investigated using current-voltage (I-V) and capacitance/conductance-voltage (C/G-V) measurements. It is found that the ideality factor (n) decreases while zero-bias barrier height (Phi(Bo)) increases with increasing temperature. The conventional Richardson plot [ln(I-o/T-2) vs. 1000/T] shows a linearity above about 200 degrees K. From the slope and intercept of the linear region, the values of activation energy (E-a) and Richardson constant (A*) were found to be 0.15 eV and 1.24 x 10(-8) A cm(-2) K-2, respectively. Then, the values of mean barrier height and A* were determined from the modified Richardson plot [ln(I-0/T-2)-q(2)sigma(2)(0)/2k(2)T(2) vs. 1000/T] and found to be 1.06 eV and 33.87 A cm(-2) K-2, respectively. The calculated A* value is very close to the theoretical value of 32 A cm(-2) K-2 for p-type Si. The obtained results indicate that Al/CuFeO2/p-Si/Al diode can be used as a temperature measurement sensor for low-temperature controlling applications.
Keywords: Schottky-Barrier Diodes; Cufeo2 Thin-Films; Electrical Characteristics; Conductance Technique; Glass Substrate; Dependence; Interface; Frequency; Parameters; Deposition